Implementation Of National Character Education (Study Of ‎Scouting Activities Analysis At Man 2 Karanganyar)‎ - Ahmad Muhtadi (ATTARBIYAH: Journal of Islamic Culture and Education, 2019)
This research is aimed to describe various forms of students’ character nurturing through scouting activities at MAN 2 Karanganyar. This research also studied a number of constraints emerging within the nurturance of the students’ character and efforts made to overcome the constraints. It was a descriptive research study employing a qualitative approach. The subjects were selected using a purposive sampling technique. The data were collected through participatory observation, interviews, and documentation. The data were then analyzed using an inductive analysis technique. The results showed that character building through scouting activities at MAN 2 Karanganyar by maximizing the roles of the scout nurturers as partners or supervisors, gave supports and facilitated students with modern, interesting, and challenging activities. Among the methods used were: the implementation of scouting codes of respects in every activity; learning activities through doing, working in groups, cooperating, and competing; activities in the open air such as camping; rewards in the forms of capacity symbols such as bantara and laksana; and separate units of ambalan for males and females. The constraints emerging were, among others, a lack of teachers’ attention to the scouting issues and the great number of students who did not like to join scouting activities. The solution was through inviting all the teachers to willingly contribute to the scouting activities and creating interesting and challenging activities for the students